2018
DOI: 10.1038/s41477-018-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

Organelle DNA degradation contributes to the efficient use of phosphate in seed plants

Abstract: DNA retained in the endosymbiotic organelles-chloroplasts and mitochondria-of seed plants influences growth in phosphate-limited conditions through a degradation mechanism implemented by DPD1 exonuclease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Plastid and mitochondrial DNAs in plants cells are organized in nucleoids [ 44 , 45 ]. The organization and distribution of chloroplast nucleoids can indicate chloroplast differentiation or degradation status [ 46 , 47 ] and, as chloroplast nucleoids are important in chloroplast gene expression, development, and phosphate supply, their analysis can provide valuable information regarding leaf physiology [ 48 , 49 , 50 , 51 , 52 ]. Therefore, we questioned whether chloroplast nucleoid formation might be affected in chlorosis-inducing mutants such as Ar50-33-pg1.…”
Section: Resultsmentioning
confidence: 99%
“…Plastid and mitochondrial DNAs in plants cells are organized in nucleoids [ 44 , 45 ]. The organization and distribution of chloroplast nucleoids can indicate chloroplast differentiation or degradation status [ 46 , 47 ] and, as chloroplast nucleoids are important in chloroplast gene expression, development, and phosphate supply, their analysis can provide valuable information regarding leaf physiology [ 48 , 49 , 50 , 51 , 52 ]. Therefore, we questioned whether chloroplast nucleoid formation might be affected in chlorosis-inducing mutants such as Ar50-33-pg1.…”
Section: Resultsmentioning
confidence: 99%
“…Dismissal of the mtDNA in germinative pollen would be because of selective degradation, and several nucleases have been identified that could be involved [71]. The degradation of organellar DNA by exonucleases could be also a mean for rapid access to phosphate when plants are exposed to nutrient-deficient conditions [72].…”
Section: Structure Of Plant Organellar Genomesmentioning
confidence: 99%
“…Rowan et al , ; Oldenburg et al , ; Shaver et al , ; Rowan et al , ), starts later, but before symptoms of senescence become visible (Baumgartner et al , ; Sodmergen et al , ) or is rather kept at high copy numbers and remains functionally active until senescence, needs to be resolved (e.g. discussion in Golczyk et al , ; Oldenburg et al , ; Sakamoto and Takami, ; Takami et al , ). Comparably, it needs to be clarified whether or not plastid genes and genomes are inactivated by mutations and degraded to non‐functional fragments in mature, photosynthetically active mesophyll cells (Kumar et al , ; Oldenburg et al , ; Kumar et al , ) or remain intact (e.g.…”
Section: Introductionmentioning
confidence: 99%